PERFORMANCE EVALUATION OF OFF-GRID SOLAR POWER PLANT FOR STREET LIGHTING AT PT. REZEKI PERKASA SEJAHTERA LESTARI WAJOK HULU WEST KALIMANTAN - Hartono, Rudi; Yandri, Yandri; Hiendro, Ayong (Faculty of Engineering, Universitas Tanjungpura, 2024)
This study aims to evaluate the performance and capacity of the Solar Power Plant (PLTS) system that has been installed on charging batteries for street lighting. Before cleaning the surface of the solar panel, the energy produced only reached 707.46Wh, and after cleaning, the energy produced increased to 859.77Wh. However, these results still do not meet the daily energy requirements for a 12-hour battery charge. The research methodology includes analyzing the impact of dust on solar panels, evaluating the performance of PLTS, and calculating daily energy requirements. Based on the PLTS battery capacity of 9600Wh, the maximum energy obtained from charging the battery is still insufficient to power two street lighting lamps for 12 hours. Therefore, an evaluation of the installed PLTS was conducted, resulting in several findings. First, it is necessary to add 11 units of solar panels with a capacity of 455Wp so that the required energy can be met. Second, the capacity of the installed battery is sufficient to meet the energy needs of the lighting. Third, the capacity of the Solar Charge Controller (SCC) needs to be increased to 150Ampere due to the addition of solar panels. Finally, the inverter that has been installed with an output of 1000Watt is adequate for the needs of the system. The results of this evaluation can serve as a basis for improving the performance of the PLTS in order to meet the desired energy needs.